1997
DOI: 10.1074/jbc.272.49.30709
|View full text |Cite
|
Sign up to set email alerts
|

A Weak TATA Box Is a Prerequisite for Glucocorticoid-dependent Repression of the Osteocalcin Gene

Abstract: The TATA box element is not only important for establishing basal levels of transcription, but it can also be used to modulate cell type or stage specific gene activity. In the case of the human osteocalcin gene, which is transcriptionally repressed by glucocorticoids, a specific binding element for the glucocorticoid receptor (GR) overlaps a noncanonical TATA box. In the present study, the relevance and function of the TATA element in glucocorticoid-mediated repression of the human osteocalcin gene was charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
1
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 31 publications
0
34
1
1
Order By: Relevance
“…GR binding sites were demonstrated in the vicinity of human (25) and rat (29) OC proximal promoter elements, the TATA box, and the OC box. It was suggested that GR binding interfered with interaction of transcription factors with the OC basal promoter (25,27,35). GR binding to distal promoter elements of the human (26) and the rat (28) OC genes was also suggested to contribute to transcriptional repression.…”
Section: Discussionmentioning
confidence: 99%
“…GR binding sites were demonstrated in the vicinity of human (25) and rat (29) OC proximal promoter elements, the TATA box, and the OC box. It was suggested that GR binding interfered with interaction of transcription factors with the OC basal promoter (25,27,35). GR binding to distal promoter elements of the human (26) and the rat (28) OC genes was also suggested to contribute to transcriptional repression.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these studies suggest that the TBP-DNA complex may exist in different structural contexts for variant sequences, and this context may also impact downstream steps in the transcription process. Because variant TATA elements play a fundamental role in the proper expression of many eukaryotic genes (9,10,21,24), it is essential to determine the mechanisms underlying differential levels of transcription from varying TATA elements.…”
Section: Discussionmentioning
confidence: 99%
“…For example, activation by E1A of the human hsp70 promoter is highly dependent on the sequence of the TATA element: substitution of the hsp70 TATA (TATAA) with the SV40 early promoter TATA (TATTTAT) results in loss of induction by E1A but not by heat shock (9). In addition, an off-consensus TATA element is essential for the proper regulation of the osteocalcin gene by glucocorticoid receptor (10). As such, the particular sequence of the TATA element is likely to be critical for appropriate gene expression of a specific gene.…”
mentioning
confidence: 99%
“…Osteoblasts seem to be the major target of glucocorticoid action in the bone. GCs decrease osteoblast number and function by altering expression of several osteoblast-specific genes in the bone, including repression of osteocalcin (Meyer et al 1997) and type I collagen (Delany et al 1995a), and induction of collagenase (Delany et al 1995b). GCs decrease IGF-I synthesis in osteoblasts, where IGF-I has been shown to have profound anabolic effects, inducing proliferation of preosteoblasts, increase in collagen I synthesis and decrease in collagenase.…”
Section: Role Of Other Hormones In Bone Remodelingmentioning
confidence: 99%